Physics for scientists and engineers - Serway, Raymond A.; Jewett, John W. (2008)
Achieve success in your physics course by making the most of what PHYSICS FOR SCIENTISTS AND ENGINEERS has to offer you. From a host of in-text features to a range of outstanding technology resources, you'll have everything you need to understand the natural forces and principles of physics. Throughout every chapter, the authors have built in a wide range of examples, exercises, and illustrations that will help you understand the laws of physics AND succeed in your course! Available with most new copies of the text is CengageNOW for Physics. Save time, learn more, and succeed in the course with this online suite of resources that give you the choices and tools you need to study smarter and get the grade. Receive a personalized study plan based on chapter-specific diagnostic testing to help you pinpoint what you need to know NOW, and interact with a live physics tutor through the exclusive Personal Tutor with SMARTHINKING program to help you master the concepts.